Urea cycle; oxidative phosphorylation 1 - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Amino acids catabolism, Urea Cycle and connections to other metabolisms, Overview of ‘energetics metabolism’
Reviewed at 2022/11/27